Jokes about godfathers in Ukrainian laughter culture context - Nikolaeva; Maksymenko (Ukrainian Cultural Studies, 2022)
The article aims to analyze jokes in Ukrainian laughter culture context. It stresses on the chosen topic relevance and researchers’ growing interest to Ukrainian national identity, national character, spiritual culture specific features and various phenomena associated with Ukrainian humor, satire, and picture of the laughter world. The article attempts to determine the place and peculiarities of a separate series of modern Ukrainian jokes, i.e. jokes about godfathers. Special attention is paid to joke as a cultural phenomenon which is due to laughter folk culture signs presence in it: various manifestations of human life parody when its ideals and values are humiliated, moral standards are devalued to affirm opposite positive ones, the absurd way of life realities presentation. The authors analyze the mechanism of comic effect occurrence in jokes which becomes possible under certain conditions when person’s everyday countless little things of life generate a comic situation which is the result of the inconsistency of the expected and true communication of man and society. The discrepancy between what has already gone but keeps on pretending to be alive creates a comic effect. The study notes that the Ukrainian laughter culture has its own peculiarities. They are the lack of devastating reflection, good-naturedness, life-affirming nature, benevolence, and self-irony. The special place of jokes about godfathers among Ukrainian jokes is emphasized. Those jokes are united in one series by their main participants of events and filled with mental humor and Ukrainian flavor. The concept ’godfather’ in Ukrainian mentality and Ukrainian jokes is revealed. The article demonstrates on concrete examples the comedy mechanism, national Ukrainian character traits embodiment in godfather’s image, ways, and technics of comic effect. The analysis of the selected material shows that jokes about best men are an important component of the laughter culture of Ukrainians. Jokes about godfathers as examples of Ukrainian laughter culture require further in-depth research, generalization and systematization. Investigations can have different directions, including the analysis of the means of creating a comic, be dedicated to the detection of the functions of the joke, its genre features.